Motivation Techniques and Strategic Approach to Motivation in FBIH Companies - Lasić, Marija; Mabić, Mirela; Lesko Bošnjak, Lidija (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
The success of a company depends on the employees, so the challenge for managers is to monitor their needs continuously and find ways to encourage them to work and achieve goals. By using a combination of compatible material and non-material techniques within motivation strategies, managers link long-term company goals and rewarding employees for work and achievements. The aim of this paper is to get insight into the used motivation techniques and strategic approach to motivation in companies in the Federation of BiH (FBiH). The survey was conducted in early 2019 and covered 63 companies. The most commonly used material motivation techniques are salaries, bonuses, and paid leave, and the most commonly used nonmaterial techniques are appropriate working hours, information on work results and the possibility of advancement. Almost half of the managers state that there are established rules for motivating employees in their companies, slightly more than ¼ point out that there is an established plan for motivating employees that is continuously implemented. Only a part of the surveyed companies, have a continuous, systematic way of monitoring employee motivation. Assessing motivation and taking corrective action is most often carried out by top management, two or more times a year. The results indicate that some companies in the FBiH have not yet realized that the human factor is a key factor in achieving better business results. In order for motivation to be truly effective, it must be approached in a planned and continuous manner.